Characteristics and risk factors of drug-resistant epilepsy in children: a retrospective study in Jakarta from 2020–2025 - Achmad Rafli; Setyo Handryastuti; Irawan Mangunatmadja; Rahmad Mulyadi; Aria Kekalih; Anggi Gayatri; Elisabeth Herini; Wisnu Ananta Kusuma; Citra Raditha; Anna Tjandrajani; Pandu Caesaria Lestari; Yarmaniani Miliati Muchtar (Paediatrica Indonesiana, 2026)
Background Epilepsy is a major chronic neurologic disorder in children. Approximately 30% of pediatric epilepsy cases are drug resistant, posing several diagnostic and therapeutic challenges, as well as social burden and economic loss. Currently, there is little data on pediatric drug-resistant epilepsy (DRE) in Indonesia. Objectives To identify the characteristics of pediatric DRE and analyze for associations of clinical, electroencephalographic, and imaging findings with seizure control status after three months of pharmacologic treatment. Methods This was retrospective study of 164 children with DRE seeking treatment in two national referral hospitals in Jakarta from 2020 to 2025. We collected data on demographic and clinical characteristics, electroencephalography (EEG) results, and brain MRI results. Seizure frequency during and after completion of the first three months of treatment was noted. Results Most patients were diagnosed at <5 years of age (65.6%). The majority of patients (64.6%) received two types of anti-seizure medications (ASMs) and had generalized seizures (84.8%). The most common ASM combination was valproic acid with levetiracetam (43.90%). Interictal electroencephalograms were mostly abnormal without epileptiform patterns (42.7%), followed by abnormal with epileptiform patterns (32.3%). On multivariate analysis, seizure type consistent with an epilepsy syndrome [RR 2.93 (95%CI 1.15 to 7.44); P=0.024], EEG consistent with an epilepsy syndrome [RR 2.21 (95%CI 1.05 to 4.64); P=0.036], and the ASM combination of valproic acid, levetiracetam, and clobazam [RR 1.58 (95%CI 1.13 to 2.21); P=0.007] were significantly associated with poor seizure control. Conclusion Children with DRE who have electroclinical features consistent with an epilepsy syndrome are more likely to have poor seizure control. The ASM combination of valproic acid, levetiracetam, and clobazam is associated with poor seizure control, but causality cannot be inferred from this study.